Unpacking the impacts of digital leadership: how digitalization is reshaping HRM in public administration governance? - Ferraz, D. (Economic sustainability potentiated by artificial intelligence, 2025)
In the contemporary era, digital technology is profoundly transforming the landscape of public administration and its human resource management (HRM). This research explores the multifaceted impacts of digitalization on HRM, focussing on its influence on work models and leadership profiles in public administration (PA). The objective is to delve into the effects of digital innovations on work models, HRM, and leadership within the context of PA. The theoretical framework considers the transition from Bureaucracy models to New Public Management and then to New Public Governance, evaluating how current models are aligned with digital transformation and digital leadership concepts. Therefore, a qualitative approach was adopted, integrating data from literature review and content analysis of relevant literature and public policy documents. This study captured insights from HRM public policies, managers, HR professionals, and other stakeholders involved in digital transformation initiatives in public administration. It was possible to identify how digital technology, particularly digital transformation, is impacting HRM and leadership profiles in the public sector. The findings highlight themes such as leadership in multicultural teams, data-driven analytics and fostering engagement of digital citizens in networks, as well as the interconnectedness of public managers’ leadership with internal and external environments. As public administration evolves in the digital age, it becomes imperative to understand the dynamics between digital technology, PA models, and HRM and leadership practices. This article seeks to fill this knowledge gap, offering valuable insights for future research and practice.